2017
DOI: 10.1016/j.juro.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characteristics of a Multigene Urine Biomarker Test for Monitoring for Recurrent Urothelial Carcinoma in a Multicenter Study

Abstract: The Cxbladder Monitor test offers combined high sensitivity and high negative predictive value to rule out urothelial carcinoma. This test has clinical utility as a confirmatory negative adjunct to cystoscopy, potentially justifying the postponement/avoidance of cystoscopic investigations to monitor recurrence in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 19 publications
1
65
0
Order By: Relevance
“…It achieved an impressive sensitivity and NPV of 91% and 96% compared with cytology (22% and 87%) for detecting BC in a study comprising 803 patients undergoing surveillance . The test also had a high sensitivity of 86% in Ta low‐grade disease . The application of the Cxbladder Monitor in patients with microhaematuria reduced the number of invasive diagnostic procedures such as cystoscopy and CT scans .…”
Section: Discussionmentioning
confidence: 99%
“…It achieved an impressive sensitivity and NPV of 91% and 96% compared with cytology (22% and 87%) for detecting BC in a study comprising 803 patients undergoing surveillance . The test also had a high sensitivity of 86% in Ta low‐grade disease . The application of the Cxbladder Monitor in patients with microhaematuria reduced the number of invasive diagnostic procedures such as cystoscopy and CT scans .…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] On the other hand, the predictive effect of a multiple gene signature has been highlighted. 32,33 In this study, we conducted GSVA to screen the most important Recent studies have revealed the involvement of EMT in the pathogenesis of cancers, including BLCA. 34 Some attribute the distinguishing characteristics between NMIBC and MIBC to differences in EMT-related programming.…”
Section: Discussionmentioning
confidence: 99%
“…This marker panel was designed to optimize sensitivity. While this has improved test performance for this goal with reported sensitivity and NPV of 93 and 97%, respectively, it does come at the cost of a low specificity [34]. Sensitivity reached 95% in recurrent disease with high risk of Prog, and false-negative findings were reported in only 1.5% of cases.…”
Section: Urinary Biomarkers For the Surveillance Of Bladder Cancer Pamentioning
confidence: 99%